2013
DOI: 10.1002/ccd.24565
|View full text |Cite
|
Sign up to set email alerts
|

Initial clinical experience with the Coherex FlatStent™ and FlatStent™ EF PFO closure system for in‐tunnel PFO closure: Results of the Coherex‐EU study

Abstract: This initial study of the Coherex FlatStent/FlatStent EF PFO Closure System demonstrated the potential for in-tunnel PFO closure. The in-tunnel Coherex FlatStent EF may offer an alternative to septal repair devices for PFO closure in appropriately selected patients; however, further investigation will be necessary to establish the best use of this device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…Undoubtedly, these numbers will improve with experience. As expected, there were zero occurrences of new atrial arrhythmias, thrombus formation or pericardial effusion, demonstrating safety and feasibility . The reluctance of physicians and regulatory bodies to replace a device with over 20 years of experience and high closure rates is understandable.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Undoubtedly, these numbers will improve with experience. As expected, there were zero occurrences of new atrial arrhythmias, thrombus formation or pericardial effusion, demonstrating safety and feasibility . The reluctance of physicians and regulatory bodies to replace a device with over 20 years of experience and high closure rates is understandable.…”
Section: Introductionmentioning
confidence: 54%
“…There is lack of data available on the performance of the Coherex Flatstent. The results of the initial clinical experience in the CE mark trial has demonstrated promising findings with reported complete closure rates of 86% and trivial shunts of 14% at 6‐month follow‐up . Undoubtedly, these numbers will improve with experience.…”
Section: Introductionmentioning
confidence: 97%
“…However, in clinical practice it was proven unsuccessful due to recoil with no anatomical modification. Furthermore, sizing balloons are large and, if successful, they may dilate too much the PFO. Use of a device that “respects” the anatomy by sitting inside the PFO as the Flatstent does . Another option is a device with an adjustable distance between the left and right atrial discs as the Premere PFO closure system (St Jude Medical) that it is well suited to close long tunnel PFO.…”
Section: Discussionmentioning
confidence: 99%
“…Long and stiff tunnels may prevent the correct positioning of devices having a fixed distance between the right and left atrial discs. Techniques advocated to face this kind of anatomy include balloon pull‐through , trans‐septal puncture , detunnelization by using the sizing balloon , and the use of specific intratunnel devices . These methods are limited by the need for an additional procedure, equipment, specific devices, and/or potential risks.…”
Section: Introductionmentioning
confidence: 99%
“…So wurden Okklu der entwickelt, die speziell an die anato mischen Gegebenheiten eines PFO ange passt sind. Hierzu gehören Systeme, die selektiv im PFOTunnel platziert wur den wie der SeptRx (SeptRx Inc., Fre mont, Kalifornien, USA) und der Cohe rex FlatStent® (Coherex Medical, Salt La ke City, Utah, USA; [38,39] …”
Section: Congenital Heart Defects · Myocardial Infarction · Embolismsunclassified